(3VhGHW GSJNOGe GdehGQO GdHTQjI aj GdGbJUGO GdESdGej hBKGQgG aj GdJfejI (B/s - (3GdbjSj, cGed UcQs ((3HjQhJ (B- (3dHfGf (B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY,s, 2017)
(3gPG GdcJGH VhGHW GSJNOGe GdehGQO GdHTQjI aj GdGbJUGO GdESdGej hBKGQgG aj GdJfejI hgh OQGSI ESdGejI JgOa Edi JbOje efgL GdESdGe aj GdJYGed eY EfSGfjI GdEfSGf hcjajI GdGSJaGOI ef GdWGbGJ GdHTQjI aj GdGbJUGO GdESdGej, aJfGhdJ eaghe hVhGHW GSJNOGe GdehGQO GdHTQjI hehba GdESdGe ef GdeTcdI GdScGfjI hYfUQ GdYed hehba GdESdGe ef JfXje GdfSd hCTcGd GdYed aj GdCbJUGO GdESdGej(B.s
(3HHdjhLQGajI (B: (3UaMI (B364-392.s
Keywords: (3GdESdGe hEOGQI GdCaQGOs; (3GdESdGe hGdEUdGM GdGbJUGOjs; (3GdGbJUGO GdESdGejs